2023
DOI: 10.1117/1.jrs.17.044506
|View full text |Cite
|
Sign up to set email alerts
|

On the possibility to map submerged aquatic vegetation cover with Sentinel-2 in low-transparency waters

Ele Vahtmäe,
Kaire Toming,
Laura Argus
et al.

Abstract: .Modifications in submerged aquatic vegetation (SAV) spatial and temporal abundance patterns indicate changes in marine environmental conditions or physical disturbances and need to be monitored. Vegetation percent cover (%cover) is recognized as one of the key parameters in SAV monitoring. Coastal waters of the Baltic Sea are often turbid and contain high amount of colored dissolved organic matter. These factors significantly reduce the water depth, where benthic parameters can be detected by remote sensing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…High-accuracy atmospheric correction is required for physicsbased bio-optical inversion models [25]. Our previous studies have shown that high-quality water surface spectra are retrieved as a result of DWC atmospheric correction [19,26]. The data visualization was performed in ENVI ® image analysis and processing software.…”
Section: Satellite Imagerymentioning
confidence: 99%
See 4 more Smart Citations
“…High-accuracy atmospheric correction is required for physicsbased bio-optical inversion models [25]. Our previous studies have shown that high-quality water surface spectra are retrieved as a result of DWC atmospheric correction [19,26]. The data visualization was performed in ENVI ® image analysis and processing software.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…The ODW mask was created based on the 12th of May 2021 S2 image using a supervised classification approach [19] and used on all the collected images (Table 1). We are aware that water transparency differences can occur between different dates, so some areas could be classified either as ODW or optically shallow water (OSW) depending on the water conditions on the specific time.…”
Section: Optically Deep Water (Odw) Maskmentioning
confidence: 99%
See 3 more Smart Citations